Implementation of Lecture Monitoring Standard Oparational Procedure In Academic Sub-Section At Faculty Of Education Unima - Tulus, Indri; Bogar, Wilson; Mandagi, Martinus (Technium Social Sciences Journal, 2021)
This study aims to describe and analyze the implementation of SOPs Monitoring lectures which consists of 8 activities at the Faculty of Education, State University of Manado. This research was conducted with a qualitative approach with descriptive research methods. Collecting data using interview, observation and documentation techniques. The data analysis technique uses an interactive model. The results of the study show that the implementation of prosedure operational standard for monitoring lectures has not been carried out in accordance with the stages so that lecture monitoring activities carried out at Faculty of Education Unima do not guarantee the creation of quality in the lecture process. Based on the results of this study, it is recommended that it is necessary to adjust SOPs, and make new lecture monitoring SOPs that are adapted to the dynamic Covid-19 pandemic situation. lecture monitoring SOPs favor students so that they are effective and efficient if applied to the learning process during the Covid-19 pandemic, and need to be there is attention from the leadership of the Faculty of Education, Manado State University in implementing SOPs for monitoring recovery and providing motivation for human resources as well as supervision from related parties to ensure that all human resources carry out tasks in accordance with their main duties and functions in order to achieve the goal of monitoring lecture, namely improving the quality lectures.